LOYALTY PERSPECTIVE ANALYSIS OF SMALL AND MEDIUM BUSINESS MARKETING ABILITY TO INNOVATE AND PERFORM GOOD - Finta Aramita (RADJA PUBLIKA, 2023)
The production environment has changed to a knowledge and technology system. Competition in the marketing system has also evolved into a more global and innovation system, becoming a competitive environment in most countries and businesses. Companies must evolve and innovate to deal with intense competition and shifting consumer demands if they hope to succeed in the long term in today's global market economy. Small and medium-sized enterprises must seek new motivations and business strategies to better develop new goods and services and take into account new information and technological advances. For businesses to grow, innovation is essential. Traditional innovation literature, first published in 1934, focuses on the factory sector, competitive markets and developed economies. Compared to other countries, Indonesia has a much higher proportion of small businesses per capita. Over the years, SMEs have contributed to developing countries in Asia (including ASEAN). Small and medium-sized enterprises are cited in ASEAN countries as a key driver of economic growth and development, the foundation of national economies, the highest-paying industry, and a potential tool for poverty reduction. Especially after the Asian financial crisis, including Indonesia.